The seeds of commerce: a network analysis-based approach to the Romano-British transport system - Orengo, Hector A.; Livarda, Alexandra (Elsevier, 2016)
Communication routes are an important subject in the study of the human past. They allowed interactions between communities and the dispersal of goods and ideas. Their study, therefore, can shed light on the way in which communities inhabited the landscape, related to each other and were affected by macro-regional trends. Many methods, such as archaeomorphological analysis and Least Cost Route modelling (LCR), have been devised and are routinely employed for the reconstruction of ancient routes. Their analysis in terms of communication, trade or historical significance, however, has usually been left unexplored. This is probably due to the connected nature of routes, which form communication networks: these are shaped by interconnected nodes and extend over territories surpassing the regional scale in such a way that even a change in a single node or link can affect the whole network. Consequently, the partial reconstruction of communication networks provided by the aforementioned methods does not usually allow a holistic analysis. In this paper the relatively well understood British Roman road network is employed to explore the analytical possibilities offered by a combination of Social Network Analysis, Spatial Network Analysis and spatial interpolation-based distribution analysis. The British road network has been reconstructed using published data but also a variation of LCR in which cost surfaces are derived from cultural data obtained from large-scale cultural inventories. The distribution of introduced food plants during the Roman period serve as an excellent proxy for the study of trade along the network and its historical consequences. This multi-period archaeobotanical dataset has some evident advantages to other types of material remains: archaeobotanical remains are not reused as, for example, amphorae and, accordingly, they reflect a distribution pattern based on consumption or commerce. Some of them are imported (as they cannot be produced locally) and, consequently, their distribution would be applied through usage of the main routes. The results suggest a continuous inflow of exotics but highlight their changing transport routes, their differential access and the particular weight of certain nodal sites in the development of this commerce with direct impact on urbanisation and the overall economy of Britannia. The Roman road network acted as a major factor in the distribution of sites, their political and economic importance and their permanence or disappearance as global economic trends changed over time.